Comparison of the Shear Bond Strengths of Ceramic Brackets Using Either a Self-Etching Primer or the Conventional Method after Intracoronal Bleaching - Fethiye Çakmak Özlü; Sibel Koçak; Mustafa Murat Koçak; Selma Elekdağ-Türk; Tamer Türk (Galenos Yayinevi, 2015)
Objective:To evaluate the initial shear bond strengths (SBSs) of ceramic brackets using either a self-etching primer (SEP) or the conventional method (CM) after intracoronal bleaching with sodium perborate and distilled water.Methods:Eighty human incisors were divided into four groups according to bleaching and bonding procedures: Group 1, bleaching was not applied and the brackets were bonded with a self-etching primer; Group 2, bleaching was not applied and the brackets were bonded with the conventional method; Group 3, intracoronal bleaching with sodium perborate was applied for three weeks and the brackets were bonded with a self-etching primer; and Group 4, intracoronal bleaching with sodium perborate was applied for three weeks and the brackets were bonded with the conventional method. A self-etching primer (Transbond Plus) was applied as recommended by the manufacturer. After SEP application, the ceramic brackets were bonded with a light-curing adhesive (Transbond XT). For the conventional method, the teeth were etched with 37% phosphoric acid. After etching, a thin uniform coat of primer (Transbond XT Primer) was applied and the ceramic brackets were bonded with a light-curing adhesive (Transbond XT). SBSs were measured after water storage for 30 days, after 1000 cycles of thermocycling between 5°C and 55°C. Bond failure location was determined with the Adhesive Remnant Index (ARI).Results:For the SEP method, there was no significant difference between SBS values of the bleaching and non-bleaching groups. Furthermore, for the conventional method, the SBS value of the non-bleaching group was not significantly different from that of the bleaching group. SBS values of the SEP method presented significant differences from those of the conventional method (p<0.001). SBS values of SEP application decreased with and without bleaching. The ARI scores did not show any significant difference among the groups (p=0.174).Conclusion:Intracoronal bleaching with sodium perborate and distilled water did not affect the SBS values of ceramic brackets.